(untitled) - Connolly, John; 1968- (New York, 2021)
"In Amsterdam, four bodies, violently butchered, are discovered in a canal house, the remains of friends and confidantes of the assassin known only as Louis. The men responsible for the murders are Serbian war criminals. They believe they can escape retribution by retreating to their homeland. They are wrong. For Louis has come to Europe to hunt them down: five killers to be found and punished before they can vanish into thin air. There is just one problem. The sixth. With John Connolly's trademark "dark, haunting, and beautifully told" (Booklist) prose and breathless twists and turns, The Nameless Ones is an unputdownable thriller that will keep you on the edge of your seat"--